Optical and microstructure characterisation of ceramic - hydroxyapatite coating fabricated by laser cladding - Pascu, Alexandru; Stanciu, Elena Manuela; Savastru, Dan; Geanta, Victor; Croitoru, Catalin (My University, 2017)
In this paper, a new approach in designing IR-absorptive Al2O3/TiO2 glass/ceramic coatings through a one-step process involving laser cladding and by using hydroxyapatite as glass and hard phase ceramic former has been described and the optical and microstructural features of the material have been emphasised. To improve the bonding of the coating to the substrate, aluminium has been added in the ceramic starter paste composition. The coated layer is formed by crystalline Ir-absorptive ceramic phases entrapped in a dominatingly amorphous glassy matrix, at the interface with the copper substrate and by a predominant glassy structure, in the upper part of the coating. The results show good absorbance of the 35 m- thick layer in the IR domain and good transparency in the 500-800 nm domain, reflecting the wavelengths corresponding to the copper substrate, coupled with a good-crack resistance and hardness, making our approach useful in designing colored solar absorber.
Keywords: Solar collectors; Reflectance; Laser cladding; Glass-ceramic phases; XRD spectroscopy